Trajectories of prices in generic drug markets: What can we infer from looking at trajectories rather than average prices? - Antonio J. Trujillo; Jose C. Gutierrez; Emmanuel E. Garcia Morales; Mariana Socal; Jeromie Ballreich; Gerard F. Anderson (Health Economics Review, 2022)
Background: Well-functioning competitive markets are key to controlling generic drug prices. This is important since over 90% of all drugs sold in the US are generics. Recently, there have been examples of large price increases in the generic market. Methods: This paper examines price trajectories for generic drugs using a group-based trajectory modelling approach (GBTM). We fit the model using quarterly price information in the IBM MarketScan claims database for the past decade. Results: We identify three dominant price trajectories for this period: rapid increase trajectories, slow decline and rapid decline. Most generic drugs show a slow or a rapid decline in price trajectories. However, around 17% of all generic drugs show rapid price increase trajectories. Conclusions: As Congress is exploring an excise tax on drugs whose list price increases faster than the rate of inflation, we discuss what drugs would be most likely to be affected by this law.
Keywords: 330; Drug; Generic drugs; Group based trajectory models; Mergers and acquisitions; Prices